Communication Tools for the Modern Doctor Bag. Physician Patient Communication Part 1: Beginning of a medical interview - Sapna Patel Kuehl (Greater Baltimore Medical Center, 2011)
Effective physician patient communication is essential to best practice in medicine. Good communication with patients is critical in making the right diagnosis, improving compliance and overall outcomes for our patients (as well as improving physician satisfaction.) Communication skills can be learned and need to be taught, practiced and given the same emphasis as other core competencies in medicine. The focus of this article is on the Calgary-Cambridge Model for physician patient communication in the context of a medical interview. The beginning of a patient encounter is discussed, with emphasis on appropriate introductions and attentive active listening.